Relationship of Stress Factors and Nutritional Status With Random Blood Glucose Levels In Pre-Elderly Type II Diabetes Patients at Grandmed Hospital Lubuk Pakam - zebua, edarni; Riska Rani Duita Simarmata; Salmi Angraini; Dian Novita (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Type II diabetes mellitus is one of the chronic metabolic diseases that remains a major cause of morbidity and mortality worldwide. Its steadily increasing prevalence each year poses significant challenges to public health systems. This study aims to analyze the relationship between stress levels and nutritional status with random blood glucose levels among pre-elderly patients with type II diabetes mellitus who were hospitalized at Grandmed Hospital, Lubuk Pakam. This quantitative study employed a correlational design. A total of 53 respondents were selected using purposive sampling based on inclusion criteria. Stress levels were measured using the Diabetes Distress Scale (DDS) questionnaire, while nutritional status was determined using the Body Mass Index (BMI). Random blood glucose data were obtained from laboratory test results and analyzed using the Spearman correlation test with a significance level of p<0.05 The analysis revealed a significant relationship between stress factors and random blood glucose levels (p=0.035), as well as between nutritional status and random blood glucose levels (p=0.026). Patients experiencing higher stress levels and excessive nutritional status tended to have higher random blood glucose levels compared to other respondents. Stress levels and nutritional status are significantly associated with random blood glucose levels among pre-elderly patients with type II diabetes mellitus. Therefore, effective stress management and proper nutritional regulation should be integral components of blood glucose control strategies to prevent long-term complications in older individuals